2013
DOI: 10.1093/mp/sst049
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of SUMO-Activating Enzyme in Arabidopsis: Implications in SUMO Conjugation

Abstract: Sumoylation is an essential posttranslational modification that participates in many biological processes including stress responses. However, little is known about the mechanisms that control Small Ubiquitin-like MOdifier (SUMO) conjugation in vivo. We have evaluated the regulatory role of the heterodimeric E1 activating enzyme, which catalyzes the first step in SUMO conjugation. We have established that the E1 large SAE2 and small SAE1 subunits are encoded by one and three genes, respectively, in the Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…It has also been established that in plants, like in mammalian and yeast cells, a SUMOylation pathway exists for SUMOylation and de-SUMOylation of proteins (23,24). More specifically, it was shown that in Arabidopsis thaliana (i) expression of isoforms of SUMO1, -2, -3, and -5 can be detected (25); (ii) conjugation of SUMO to target proteins occurs via the same sequential biochemical steps as in yeast (26,27); (iii) these reactions are catalyzed by the E1 heterodimer (SAE1a/b and SAE2), a single E2 (SCE1), and two E3 (SIZ1 and MMS2/HPY2) enzymes as well as E4-type SUMO ligases (28); whereas (iv) de-conjugation of SUMO substrates is performed by ubiquitin-like SUMO-specific proteases including ESD4 and OTS1/2 (29)(30)(31)(32)(33)(34)). It appears that in plants reversible conjugation of SUMO to target proteins is particularly important in regulating responses to abiotic environmental stresses including heat shock (35), phosphate starvation (36), drought (37), and salt stress (31), but SUMOylation of specific proteins also modifies responses to ABA signaling (38) and phytopathogen infection (39) and modulates flowering time (33).…”
Section: Significancementioning
confidence: 99%
“…It has also been established that in plants, like in mammalian and yeast cells, a SUMOylation pathway exists for SUMOylation and de-SUMOylation of proteins (23,24). More specifically, it was shown that in Arabidopsis thaliana (i) expression of isoforms of SUMO1, -2, -3, and -5 can be detected (25); (ii) conjugation of SUMO to target proteins occurs via the same sequential biochemical steps as in yeast (26,27); (iii) these reactions are catalyzed by the E1 heterodimer (SAE1a/b and SAE2), a single E2 (SCE1), and two E3 (SIZ1 and MMS2/HPY2) enzymes as well as E4-type SUMO ligases (28); whereas (iv) de-conjugation of SUMO substrates is performed by ubiquitin-like SUMO-specific proteases including ESD4 and OTS1/2 (29)(30)(31)(32)(33)(34)). It appears that in plants reversible conjugation of SUMO to target proteins is particularly important in regulating responses to abiotic environmental stresses including heat shock (35), phosphate starvation (36), drought (37), and salt stress (31), but SUMOylation of specific proteins also modifies responses to ABA signaling (38) and phytopathogen infection (39) and modulates flowering time (33).…”
Section: Significancementioning
confidence: 99%
“…The Sae2a T2 transcript, which is broadly expressed throughout maize development, encoded a truncated SAE2 polypeptide with attenuated activity (at least in vitro; Fig. 5D) and lacking the C-terminal region essential for nuclear localization in plants (Castaño-Miquel et al, 2013). And finally, the Mms21 T2 transcript skipped the second exon that encodes a predicted SUMOylation site, thus potentially altering MMS21 regulation by autoSUMOylation.…”
Section: Transcriptional Analysis Of the Sumo Systemmentioning
confidence: 99%
“…The first enzyme of the conjugation pathway (E1 or SUMOactivating enzyme [SAE]) consists of two subunits (SAE1 and SAE2), the larger of which contains the active Cys that forms a thioester bond with the C-terminal Gly of mature SUMO to activate it ( Fig. 1; Castaño-Miquel et al, 2013). SUMO is then transferred onto the Cys residue of the single subunit of the SUMOconjugating enzyme (E2 or SCE), which also interacts with SUMO and its potential target via noncovalent interactions, allowing the eventual transfer of SUMO to the «-amino group of a target Lys (Bernier-Villamor et al, 2002).…”
Section: The Sumo Conjugation and Deconjugation Systemmentioning
confidence: 99%
“…A third enzyme (E3), the SUMO ligase, plays crucial roles in target specificity and interacts with the target, the SUMO E2, and SUMO to facilitate SUMO's transfer from the E2 to the target (Yunus and Lima, 2009). In Arabidopsis, the SAE and SCE activities are encoded by single genes (SAE1 is represented by two genes, but SAE2 is encoded by only one gene), and null mutations lead to embryonic lethality (Saracco et al, 2007;Castaño-Miquel et al, 2013). On the other hand, several ligases have been identified in Arabidopsis, including the main E3 ligases SAP and MIZ (SIZ1) and METHYLMETHANE SULFONATE SENSITIVITY21 (MMS21)/HIGH PLOIDY2 (HPY2).…”
Section: The Sumo Conjugation and Deconjugation Systemmentioning
confidence: 99%